Analisis Uang Beredar Sebagai Katalisator Antara Kemiskinan Dan Peningkatan Ipm Tahun 2011-2023 Di Indonesia - Ainur Oktania; Dwi Silfani; Gresia Septina Sitohang; Frandika Situmorang; Muhammad Aldi Akbar (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
This study aims to analyze the direct and indirect effects of the percentage of poverty and money supply (M1) on the Human Development Index (HDI) in Indonesia using the path analysis method on time series data for the period 2011-2023. The independent variables analyzed are the percentage of poverty and money supply, while HDI is the dependent variable. The data used was obtained from the Central Bureau of Statistics (BPS) and related official government publications. To ensure the validity of the model, classical assumption tests were conducted, including normality, autocorrelation, and heteroscedasticity tests. The results of the analysis show that poverty percentage has a significant negative effect on HDI, both directly and through money supply, while money supply has a significant positive effect on HDI. These findings indicate that poverty reduction and efficient money supply management are crucial to improving the quality of human development in Indonesia. The proposed policy implications include the implementation of more integrated fiscal and monetary policies to promote inclusive and sustainable economic growth.